Clinical features and survival among children with retinoblastoma in Uganda - Waddell, Keith M; Kagame, Kenneth; Ndamira, Andrew; Twinamasiko, Amos; Picton, Susan V; Simmons, Ian G; Johnston, W Tom; Newton, Robert (British Journal of Ophthalmology., 2015)
Aims To characterise the clinical features, treatment and outcome of children diagnosed with retinoblastoma in Uganda. Methods The study comprised a 6-year nationwide enrolment with follow-up. Results In total, 282 cases were enrolled, 26% (72) were bilateral; 6% were lost to follow-up. Almost all diagnoses in the first affected eye were International Classification of Retinoblastoma group E or worse. Histology was available for 92%; of those, 45%, had extraocular tumour at diagnosis. Enucleation of the first eye was done for 271; 94 received radiotherapy to the socket and in the last 2 years, 70 children received chemotherapy. At close of study, 139 children had died. Survival, as determined in a proportional hazards model adjusted for age, sex, laterality and treatment era (pre or post introduction of chemotherapy), varied by extent of the tumour (p<0.001); children with only intraocular involvement were 80% less likely to die (HR=0.21, 95% CI 0.12 to 0.35) compared with children with extraocular involvement. Conclusions Diagnostic delay results in relatively high mortality among children with retinoblastoma in Uganda. There is an urgent need for more effective treatment modalities, particularly chemotherapy, and nationwide efforts to encourage earlier access to medical care.
Keywords: Clinical features; survival among children; retinoblastoma in Uganda